Belarusian social transformation model in the context of globalization of risks - Anohina, Victoria V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The main purpose of this article is to analyze the correspondence of the priorities of the social transformation modelimplemented in Belarus to the basic characteristics of the national mentality and the traditional values. It compares theGerman, Scandinavian and East Asian models of modernization, emphasizes their pros and cons in terms of adapting thesedevelopment strategies to the Belarusian realities. Thus, a primary thesis of the article is that, in the XXI century, the failureof the national transformation strategy may entail a progressive lag in the country’s socio-economic development. The lowefficiency of the current transformation model is due not only to the lack of systemic and strategic vision, but also to theinadequacy of the reforms to the objective challenges of time and the peculiarities of the national mentality. Of course, thesuccess of modernization in the era of late modernity is largely determined by its technical, technological and socio-economic parameters. However, no less important is their relevance to the dynamics of citizens’ expectations, new forms of theiridentity, and its accordance to the axiological structure of the ethno-cultural tradition.
Keywords: social transformation; modernization; globalization of risks; national mentality; cultural tradition